Faktor-faktor yang mempengaruhi kompetensi petani dalam melakukan usahatani ikan air tawar di kecamatan Polanharjo kabupaten Klaten - Erlin Yusliana; Sapja Anantanyu; Eksa Rusdiyana (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
Ability is an individual capacity to do various tasks in a profession or activity. This study aimed at scrutinizing the internal factors (age, education level, farming experience, and cosmopolitan level) and external factors (the roles of agricultural extension officers, the roles of the heads of farmer groups, local government support, and access to mass media) of the farmers in practicing freshwater fish farming in Polanharjo Sub-district, Klaten Regency, and the correlation between both the internal and external factors and farmers’ ability in practicing freshwater fish farming in Polanharjo Sub-district, Klaten Regency. This research applied a qualitative method with a survey technique. The research location was determined by considering that Polanharjo Sub-district in Klaten Regency Further, Nganjat Village, and Janti. Samples were taken using proportional random sampling, involving 60 respondents. Data were analyzed using Spearman’s rank correlation test with IBM SPSS 20.0. The results of this study include three major points. The farmers’ age and education levels were considered high, while their farming practice experience and cosmopolitan levels were low. The role of agricultural extension officers and the support of the local government was low, while the role of heads of farmer groups and access to mass media was very low. The roles of agricultural extension officers and the heads of farmer groups had a highly significant relationship with the farmers' ability to practice freshwater fish farming. Nevertheless, Farmers' age, education level, farming experience, and cosmopolitan level, local government support, and access to mass media did not show any noteworthy relationship with farmers’ ability to practice freshwater fish farming.